On Ricci Curvature of Certain Submanifolds in a Cosymplectic Space Form - Liu, Ximin; Zhou, Jianbin (Sarajevo Journal of Mathematics, 2024)
In this paper, we obtain some sharp inequalities between the Ricci curvature and the squared mean curvature for slant, bi-slant and semi-slant submanifolds in cosymplectic space forms. Estimates of the scalar curvature and the k-Ricci curvature, in terms of the squared mean curvature, are also proved respectively. 2000 Mathematics Subject Classification. 53C40, 53C15